The great reversal - Tommy Chrimes; Bram Gootjes; M. Ayhan Kose; Collette Wheeler (Koç University-TÜSIAD Economic Research Forum (ERF), 2024)
The shock of the pandemic and subsequent overlapping crises has led to a reversal in development by exacerbating the challenges facing the most vulnerable 75 economies eligible for concessional loans and grants from the World Bank's International Development Association (IDA). Over 2020-24, per capita incomes in half of IDA countries-the largest share since the start of this century-have been growing more slowly than those of wealthy economies. One out of three IDA countries is poorer than it was on the eve of the pandemic. Poverty remains stubbornly high, hunger has surged, and, amid fiscal constraints and rising investment needs, the development outlook could take an even bleaker turn-especially if weak growth prospects persist. IDA countries have several important demographic and resource advantages that could-if leveraged effectively-help close development gaps. Reaping the benefits of their advantages and meeting investment needs will require them to undertake comprehensive policy measures to bolster fiscal and monetary frameworks, enhance human capital development, and improve the quality of institutions. These policies should be complemented with significant and consistent international financial support as well as strong cooperation on global policy issues.
Keywords: E6; F00; I00; J11; O1; Q00; 330; International Development Association; IDA; stagnation; convergence; development gap